ESTUDIO DE LOS REMAKES ESTRENADOS EN ESPAÑA EN EL SIGLO XXI - Dra. Gloria GÓMEZ-ESCALONILLA,Lcda. Sofía RIESCO GADEA, (Fonseca, Journal of Communication, 2023)
The main objective of this article is to know and characterize the remakes that have been screened in the Spanish cinemas since the beginning of the 21st century. Through the study of the 162 remakes exhibited between 2000 and 2016, it is possible to know different production and market characteristics of these films and even their relationship with the original films. This study, however, does not reveal anything new regarding the situation of the cinema industry in our country, since also in the field of the remake the dominance of Hollywood is unquestionable: it makes the most remakes, mainly based on its own previous filmography, and when versioning foreign films, it adapts them to their culture. This is a culture that it successfully exports, at least to Spain, as the American remakes are also the ones with the largest audience and the highest-grossing.